2D fracture analysis of magnetoelectroelastic composites by the SBFEM. (15th November 2015) - Li, Chao; Tong, Liyong
Abstract: This paper extends the scaled boundary finite element method (SBFEM) to 2D fracture analysis of magnetoelectroelastic composites. The generalized extended stress intensity factors, i.e., the stress intensity factors, the electric displacement intensity factor and the magnetic induction intensity factor, for different crack configurations and material combinations are evaluated. The governing equations of the SBFEM for magnetoelectroelastic materials are derived based on the virtual work principle. The generalized extended stress intensity factors are determined from the solution of the singular stress, electric displacement and magnetic induction fields by extending the definition of the generalized stress intensity factors. The electrically and magnetically impermeable and permeable crack face boundary conditions are implemented and discussed. Numerical examples including the cracks in magnetoelectroelastic materials, the interface cracks between magnetoelectroelastic bimaterials and magnetoelectroelastic bimaterial wedge are presented to validate the proposed technique. The accuracy of the proposed technique is verified by comparison with the reference results.